2016
DOI: 10.1364/oe.24.002850
|View full text |Cite|
|
Sign up to set email alerts
|

Regular oscillations and random motion of glass microspheres levitated by a single optical beam in air

Abstract: We experimentally report on optical binding of many glass particles in air that levitate in a single optical beam. A diversity of particle sizes and shapes interact at long range in a single Gaussian beam. Our system dynamics span from oscillatory to random and dimensionality ranges from 1 to 3D. The low loss for the center of mass motion of the beads could allow this system to serve as a standard many body testbed, similar to what is done today with atoms, but at the mesoscopic scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…As shown in Figure 8, we can see that even N=9, there is still an observable and clear prethermalization. It is reported that up to 11 micro(nano)spheres can be trapped collectively, more than 50 atoms can be trapped and manipulated . Furthermore, the trapping frequency of each nanosphere can be adjusted, which indicates our protocol is promising for existing experimental technologies.…”
Section: Prethermalizationmentioning
confidence: 94%
See 1 more Smart Citation
“…As shown in Figure 8, we can see that even N=9, there is still an observable and clear prethermalization. It is reported that up to 11 micro(nano)spheres can be trapped collectively, more than 50 atoms can be trapped and manipulated . Furthermore, the trapping frequency of each nanosphere can be adjusted, which indicates our protocol is promising for existing experimental technologies.…”
Section: Prethermalizationmentioning
confidence: 94%
“…Multiple dielectric particles can be levitated simultaneously, and the optical fields can generate forces between them in a phenomenon called “optical binding”, which may induce the self‐organization phenomenon . While there are several studies on optical binding of the particles in liquid, the optically bonded dielectric particles in vacuum have just begun to attract attention.…”
Section: Introductionmentioning
confidence: 99%
“…Optically induced rotation can be due to optical torque [25,26] on mechanically stabilized (although such stabilization can entail losses or multiple drains) or optically levitated objects (accessible for sub-kg systems and length scales down to the diffraction limit) [26,31,32]. While optical levitation has not been applied to a photonic crystal, several promising experiments [33,34] on the rotation and translation of arrays of trapped particles suggest that this is feasible.…”
Section: Gatementioning
confidence: 99%
“…Unable to further pursue this research with the technology of his time, Ashkin urged researchers to resolve the puzzle of the colliding droplets with high-speed photography. Recently, there has been renewed interest in this attempt [7][8][9]. Notably, Moore et al [8] have observed oscillations of two silica particles for up to a few minutes.…”
mentioning
confidence: 99%
“…Recently, there has been renewed interest in this attempt [7][8][9]. Notably, Moore et al [8] have observed oscillations of two silica particles for up to a few minutes. We were able to finally achieve the demanding spatial and temporal resolutions necessary to observe the droplet motion by constructing an optical levitation setup that includes a long-distance microscope and high-speed movie camera.…”
mentioning
confidence: 99%